Assessment of doctor's satisfaction with governmental hospital after the war 2024 in Sudan - Ali Omer (International Journal of Medical Students)
BACKGROUND: After the war in Sudan, and especially after the occupation of the city of Madani, a large number of people   were displaced to the city of Port Sudan, including doctors. There was great pressure on government hospitals in Port Sudan and therefore doctors.